Training on Using the "Decision Analysis" Module in the POM-QM for Windows Software in Carrying Out Decision Analysis for Final Decision Making - Marendra, I Gede; Aryata, I Made; Afgani, Irmawan; Ramanyanti, Gina (Indonesian Journal of Advanced Social Works, 2023)
Business professionals often face difficulties in their work or business so they can quickly offer the best solutions when making decisions. Decision analysis is an important process in making effective and efficient decisions in various contexts, both in personal life and in the world of business and organizations. In decision analysis, several aspects that need to be considered include identifying problems or opportunities, collecting relevant data, situation modeling, risk assessment, determining alternatives, and selecting and implementing decisions. POM-QM for Windows is a program used to solve quantitative management problems in the operations and production domains. With POM QM for Windows training, participants are able to solve complex Decision Analysis problems quickly and precisely.